NO Augments Endothelial Reactivity by Reducing Myoendothelial Calcium Signal Spreading: A Novel Role for Cx37 (Connexin 37) and the Protein Tyrosine Phosphatase SHP-2. Issue 12 (December 2017) - Pogoda, Kristin; Mannell, Hanna; Blodow, Stephanie; Schneider, Holger; Schubert, Kai Michael; Qiu, Jiehua; Schmidt, Andreas; Imhof, Axel; Beck, Heike; Tanase, Laurentia Irina; Pfeifer, Alexander; Pohl, Ulrich; et al.
Abstract : Objective—: Because of its strategic position between endothelial and smooth muscle cells in microvessels, Cx37 (Connexin 37) plays an important role in myoendothelial gap junctional intercellular communication. We have shown before that NO inhibits gap junctional intercellular communication through gap junctions containing Cx37. However, the underlying mechanism is not yet identified. Approach and Results—: Using channel-forming Cx37 mutants exhibiting partial deletions or amino acid exchanges in their C-terminal loops, we now show that the phosphorylation state of a tyrosine residue at position 332 (Y332) in the C-terminus of Cx37 controls the gap junction–dependent spread of calcium signals. Mass spectra revealed that NO protects Cx37 from dephosphorylation at Y332 by inhibition of the protein tyrosine phosphatase SHP-2. Functionally, the inhibition of gap junctional intercellular communication by NO decreased the spread of the calcium signal (induced by mechanical stimulation of individual endothelial cells) from endothelial to smooth muscle cells in intact vessels, while, at the same time, augmenting the calcium signal spreading within the endothelium. Consequently, preincubation of small resistance arteries with exogenous NO enhanced the endothelium-dependent dilator response to acetylcholine in spite of a pharmacological blockade of NO-dependent cGMP formation by the soluable guanylyl cyclase inhibitor ODQ (1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxalin-1-one). Conclusions—: Our results identify a novel mechanism by which NO can increase the efficacy of calcium, rising vasoactive agonists in the microvascular endothelium. Abstract : Supplemental Digital Content is available in the text.